An algorithm for detection of intersections between polygonal objects by oriented bounding boxes - Zakharov, A.A.; Sadykov, S.S. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2003)
The problem on detection of intersections between objects with the use of bounding boxes is considered. The examples of bounding boxes most frequently used in practice are briefly described. Several criteria of accuracy for approximation and rate of detection are discussed. An improved algorithm for detection of intersection by oriented bounding boxes is proposed.